2012
DOI: 10.1016/j.bpj.2012.01.036
|View full text |Cite
|
Sign up to set email alerts
|

A Desolvation Model for Trifluoroethanol-Induced Aggregation of Enhanced Green Fluorescent Protein

Abstract: Studies of amyloid disease-associated proteins in aqueous solutions containing 2,2,2-trifluoroethanol (TFE) have shown that the formation of structural intermediates is often correlated with enhanced protein aggregation. Here, enhanced green fluorescent protein (EGFP) is used as a model protein system to investigate the causal relationship between TFE-induced structural transitions and aggregation. Using circular dichroism spectroscopy, light scattering measurements, and transmission electron microscopy imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…2,2,2‐trifluoroethanol (TFE) is the most commonly used cosolvent to investigate the propensity of proteins to fold into an α‐helical structure . Disordered proteins can undergo a gradual coil‐to‐helix transition as increasing amounts of TFE are added to the solution and this behavior was also observed by CD spectroscopy for the five investigated proteins (Fig. A–E).…”
Section: Resultsmentioning
confidence: 78%
“…2,2,2‐trifluoroethanol (TFE) is the most commonly used cosolvent to investigate the propensity of proteins to fold into an α‐helical structure . Disordered proteins can undergo a gradual coil‐to‐helix transition as increasing amounts of TFE are added to the solution and this behavior was also observed by CD spectroscopy for the five investigated proteins (Fig. A–E).…”
Section: Resultsmentioning
confidence: 78%
“…It is not surprising that GFP 1-10 is in an aggregated state, even the robust mature GFP can be coaxed to aggregate upon the addition of 2,2,2-trifluoroethanol (TFE), a chemical commonly used to induce aggregation in proteins. 30 The observation that CA-GFP is not as aggregated then supports the hypothesis that it is more ordered than GFP [1][2][3][4][5][6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 76%
“…Alcohols, particularly the fluorinated alcohol 2,2,2-trifluoroethanol (TFE), are perhaps the most used type of co-solvents to investigate protein aggregation and have been used in the past to study αS in vitro under shaking/stirring conditions. 30 , 31 Here we have used quiescent conditions and found that low concentrations of alcohols such as methanol (MeOH) or TFE (see Fig. S3 † for the analysis of other types of alcohols), increased significantly the rate of αS aggregation (100 μM αS in PBS buffer pH 7.4, 37 °C, in quiescence; these conditions have been used for all further aggregation experiments) and increasing concentrations of alcohols resulted in shortened aggregation lag times ( Fig.…”
Section: Resultsmentioning
confidence: 98%